Antiviral Action and Cellular Toxicity of Four Thymidine Analogues: 5-Ethyl-, 5-Vinyl-, 5-Propyl-, and 5-Allyl-2′-Deoxyuridine - Cheng, Yung-Chi (1976)
5-Ethyl-, 5-vinyl-, 5-propyl-, and 5-allyl-2′-deoxyuridine (dUrd) had antiviral activity against herpes simplex type 1 and type 2 grown in HeLa TK(−) cells, in the order 5-vinyl-dUrd, 5-ethyl-dUrd, 5-propyl-dUrd, 5-allyl-dUrd, but they were inactive against a TK(−) mutant of herpes simplex type 1. The antiviral activity of these compounds could be partially reversed by thymidine. Except for 5-vinyl-dUrd, they were not toxic to WI-38 and HeLa TK(−) cells at a concentration of 25 μM. All four analogues inhibited the growth of herpes simplex type 1-transformed HeLa TK(−) cells at a concentration of 1 μM.